Consumer Preferences for Coffee Drink Product Attributes Using the Conjoint Method in Belikopi Driyorejo, Gresik Regency - Putri, Netta Aprillia Andaresta; Mubarokah, Mubarokah; Setiawan, Risqi Firdaus (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
As time goes by, the number of coffee shop competitors in Driyorejo District, Gresik Regency is increasing and competition between coffee drink business actors is becoming more competitive, so Belikopi Driyorejo must be able to meet the needs and desires of its consumers. This research aims to analyze the level of importance of coffee drink product attributes and analyze consumer preferences for coffee drink products in Belikopi Driyorejo based on their utility value. The research method used is conjoint analysis, namely identifying a set of attributes that consumers most like and dislike and determining the importance of each attribute analyzed, namely price, taste, presentation, atmosphere, packaging, menu variants and facilities. The analysis results show that the menu variant attribute has the highest level of importance. The order of importance of attributes starts from the most important, namely menu variants, presentation method, price, atmosphere, taste, facilities and packaging. Consumer preferences regarding coffee drink purchasing decisions refer to the choice of moderately priced coffee drinks (Rp. 10,000 – 12,000), sweet coffee drink taste, cold (ice) serving method, calm coffee shop atmosphere, packaging size upgrade, caramel macchiato menu variant, and air conditioning facilities at the Belikopi Driyorejo coffee shop.